2014
DOI: 10.1007/s10964-014-0103-1
|View full text |Cite
|
Sign up to set email alerts
|

From the School Yard to the Squad Car: School Discipline, Truancy, and Arrest

Abstract: Since the 1990's, implementation of zero tolerance policies in schools has led to increased use of school suspension and expulsion as disciplinary techniques for students with varying degrees of infractions. An unintended consequence of zero tolerance policies is that school suspension or expulsion may increase risk for contact with the juvenile justice system. In the present study, we test how forced absence from school via suspension or expulsion and chosen absence from school (truancy) are associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(153 citation statements)
references
References 31 publications
6
141
0
1
Order By: Relevance
“…However, previous research [28,29] has identified perceived peer prejudice in school to be a factor related to negative experiences and behaviors in the school environment among adolescents including but not limited to unexcused absences and/or truancy, violence and aggression, and bullying [28][29][30].…”
Section: The Relationship Between Perceptions Of Peer Prejudice and Smentioning
confidence: 99%
“…However, previous research [28,29] has identified perceived peer prejudice in school to be a factor related to negative experiences and behaviors in the school environment among adolescents including but not limited to unexcused absences and/or truancy, violence and aggression, and bullying [28][29][30].…”
Section: The Relationship Between Perceptions Of Peer Prejudice and Smentioning
confidence: 99%
“…Adolescent bullies who are forcefully suspended from school are also more likely to become subsequently involved in the juvenile justice system (Fabelo et al 2011;Gonsoulin et al 2012;Wald and Losen 2003). Ironically, this may be especially true for adolescents with fewer behavioral problems prior to suspension (Monahan et al 2014). Several states have made even clearer moves towards criminalization, by modifying existing criminal law, or creating new crimes specific to bullying (Cornell and Limber 2015).…”
Section: Adolescence and The Juvenile Justice Systemmentioning
confidence: 99%
“…Schools need to emphasize that if students miss a certain number of days, they will be in danger of failing a class or facing other consequences, as students need to be accountable for their choices and behaviors [21].…”
Section: Sanctions For Truancymentioning
confidence: 99%